2014
DOI: 10.5888/pcd11.130400
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Access to Diabetes Prevention Program Sites: New York State Department of Health

Abstract: Map. This map displays existing and potential Diabetes Prevention Program sites in New York State, by county, 30minute drive-time boundaries to existing sites, and prediabetes risk factor scores. Approximately 80.0% of New York's population resides within a 30-minute drive time to a Diabetes Prevention Program site; however, most people living in 10 of the counties with the highest prediabetes risk-factor score live at a distance beyond a 30-minute drive to an existing site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The resulting maps enabled us to communicate effectively with decision makers and engage communities. GIS has helped to visualize community assets, including certified mammography facilities, locations offering lifestyle change programs (26,27), and retail outlets offering healthy food (28), and to identify gaps and plan local action. In program monitoring, local partners provide information about community locations where evidence-based interventions are implemented (26,28).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting maps enabled us to communicate effectively with decision makers and engage communities. GIS has helped to visualize community assets, including certified mammography facilities, locations offering lifestyle change programs (26,27), and retail outlets offering healthy food (28), and to identify gaps and plan local action. In program monitoring, local partners provide information about community locations where evidence-based interventions are implemented (26,28).…”
Section: Introductionmentioning
confidence: 99%
“…This approach capitalizes on geographic location as a principal variable, 18 which reflects variation in a wide range of place-based characteristics associated with health. 19,20 This information may include but is not limited to age, 30 education, 43 income, 29,43 racial segregation, 14,44 employment, 45 household composition, 14,43 healthcare access, 14,31 comorbidities, 46,47 availability of recreational facilities, 19,29 and quality of food sources. 15,19 Geographic location reflects multivariate effects of unequal distribution of resource and its influences on physical and social environments.…”
Section: Discussionmentioning
confidence: 99%
“…26 These areas can be characterized using geo-referenced databases to identify environmental, social, economic, and healthcare resources shared by residents. 26–29 The spatial patterns of Type 2 diabetes have been linked to community resources for care or prevention, 30,31,17 and have helped to inform the design of interventions to reduce diabetes-related health disparities. 26,32,33 …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Recent efforts are underway to identify health-care and income resources that are geographically separated from populations with the highest need and worst outcomes. [37][38][39][40] Improving geographic access to social service agencies that provide income support and job training could improve utilization by the populations most in need of these services. It has been previously shown that children living in poverty, but utilizing TANF, are three times more likely to have health insurance compared to children living in poverty without TANF.…”
Section: Discussionmentioning
confidence: 99%